Mütterliche Affektabstimmung von Müttern mit Missbrauchserfahrungen in der Mutter-Kind-Interaktion = Maternal affect regulation of mothers with a history of abuse in mother-infant-interaction - Kreß, Sandra; Cierpka, Manfred; Möhler, Eva; Resch, Franz (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2012)
Summary Maternal Affect Regulation of Mothers with a History of Abuse in Mother-Infant-Interaction Maternal intuitive skills can be threatened as a result of severe deprivation or unresolved trauma in the own childhood and can even be inaccessible to the mother. A mother’s own childhood experience of abuse maybe a risk factor for repeated child abuse. As a follow-up study to assess the emotional availability of abused mothers it was investigated how a physical or sexual abuse appears in the mother-child interaction and communication in the context of “cycle of abuse” and whether it could give effect to it. Interactions of mothers with abuse experience were compared with those of mothers without an abuse experience and evaluated five months postpartum with the Munich clinical communication scale (MKK). The results suggest that maltreatment experienced mothers show less emotion tuning to their child in a standardized interaction sequence.